Uneven geographies of COVID-19 II: spatialities and economic geographies in a syndemic - Bork-Hüffer, Tabea; Everts, Jonathan; Butsch, Carsten (Geography compass, 2025)
This second of three review articles on the uneven geographies of COVID-19 examines geographical research on (1) spatial patterns of the pandemic's unfolding and (2) its uneven economic geographies, considering both its direct and indirect impacts—for example, those resulting from related preventive measures. In line with this article series, it (3) concludes by discussing the relevance of the reviewed research for the syndemics approach and vice versa. Research on economic effects analyzes disruptions to global value chains, industries, labor systems, and workspaces, particularly remote work. Some studies explore how the pandemic coincided with ongoing economic transitions such as economic restructuring and shrinkage, austerity politics, digitization, and automation. Studies highlight the need to contextualize spatial inequalities within historical political-economic interdependencies, power asymmetries, and structural disparities. In doing so, geographical studies add depth to syndemic analyses of structural vulnerabilities and crisis cascades, highlighting the need for spatially sensitive assessments. Still, diverging findings at national, regional, and local levels call for comparative ex-post analyses and relational methodologies able to unpack syndemic complexities. In turn, geographers can benefit from syndemic scholars' insights into disease burdens and pre-existing structural health impacts.
Gesehen am 08.04.2025